2019
DOI: 10.3389/fpsyg.2019.02704
|View full text |Cite
|
Sign up to set email alerts
|

Music Education at School: Too Little and Too Late? Evidence From a Longitudinal Study on Music Training in Preadolescents

Abstract: It is widely believed that intensive music training can boost cognitive and visuo-motor skills. However, this evidence is primarily based on retrospective studies; this makes it difficult to determine whether a cognitive advantage is caused by the intensive music training, or it is instead a factor influencing the choice of starting a music curriculum. To address these issues in a highly ecological setting, we tested longitudinally 128 students of a Middle School in Milan, at the beginning of the first class a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 68 publications
3
19
0
Order By: Relevance
“…Language is one of the far transfer domains most extensively examined in the music training literature. Many studies examine transfer to linguistic abilities including phonological awareness (e.g., Vidal et al, 2020), reading (e.g., Carioti et al, 2019), speechin-noise perception (e.g., Hennessy et al, 2021), speech-in-quiet perception (e.g., Tierney et al, 2015), or prosody perception (e.g., Moreno et al, 2009). Although results from individual studies vary (e.g., Boebinger et al, 2015;Mehr et al, 2013), the mechanisms underlying associations between music and linguistic processing have been discussed.…”
Section: Neurobehavioral Effects Of Music Trainingmentioning
confidence: 99%
“…Language is one of the far transfer domains most extensively examined in the music training literature. Many studies examine transfer to linguistic abilities including phonological awareness (e.g., Vidal et al, 2020), reading (e.g., Carioti et al, 2019), speechin-noise perception (e.g., Hennessy et al, 2021), speech-in-quiet perception (e.g., Tierney et al, 2015), or prosody perception (e.g., Moreno et al, 2009). Although results from individual studies vary (e.g., Boebinger et al, 2015;Mehr et al, 2013), the mechanisms underlying associations between music and linguistic processing have been discussed.…”
Section: Neurobehavioral Effects Of Music Trainingmentioning
confidence: 99%
“…However, scientific evidence that supports these effects of music mainly exists as anecdotal, observational, or in non-randomized and non-controlled interventional studies. Even in the absence of unequivocal evidence on the impact of music on cognitive development, musical education remains a desirable ability in children and curricular education programs worldwide (Carioti et al, 2019 ). When evaluating these associations, it may be convenient to point at specific cognitive processes influenced by music rather than assessing cognitive development altogether.…”
Section: Introductionmentioning
confidence: 99%
“…These findings suggest that IQ may be stable over time in standard Japanese children in the absence of special intervention. In the international literature, it is also known that music training (Carioti et al, 2019 ), video games, and video viewing can increase WISC scores (Soares et al, 2021 ). However, in the present study, these particular types of training were also rarely observed in a sustained manner during the observation period.…”
Section: Discussionmentioning
confidence: 99%